Protection of Human Rights and Freedoms in the Administrative Proceedings of the European Union - Oleksandr Rastorhuiev; Petro Makushev; Alla Pukhtetska; Andriy Hridochkin; Irina Smaznova (Hasanuddin Law Review, 2021)
Since there is a problem of forming a system of modern doctrinal knowledge on protection in administrative proceedings by individuals of their rights violated in public relations, the topic under research becomes relevant. The justice in national administrative cases requires qualitative improvement taking into account European experience. The purpose of the research is to form a uniform judicial enforcement in the field of public relations, establish the rule of law, and provide fair justice. The methodological basis of this study is a set of general scientific (dialectical, analysis, and synthesis), as well as special legal (historical, comparative law, consideration and interpretation of legal norms, formal-logical) methods of scientific knowledge. The practical significance of the obtained results is that the formulated theoretical provisions, proposals and recommendations can be used: in research to conduct further research on the problems of administrative proceedings in Ukraine, ways and means of effective protection of subjective rights of individuals; in law-making for further improvement in accordance with European principles of national legislation; in the law enforcement practice of judges of administrative courts of Ukraine for consideration and resolution of public law disputes, in the protection of their rights in administrative judicial specialization by citizens and legal entities.